2022
DOI: 10.1038/s41526-022-00194-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of microgravity on bone structure and function

Abstract: Humans are spending an increasing amount of time in space, where exposure to conditions of microgravity causes 1–2% bone loss per month in astronauts. Through data collected from astronauts, as well as animal and cellular experiments conducted in space, it is evident that microgravity induces skeletal deconditioning in weight-bearing bones. This review identifies contentions in current literature describing the effect of microgravity on non-weight-bearing bones, different bone compartments, as well as the skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 151 publications
(258 reference statements)
0
39
0
2
Order By: Relevance
“…In addition, the mRNA expression levels of the osteoblastic markers, Col1a1 and Ocn, in the simulated microgravity treatments were significantly lower than that in the 1G control (Figure 5). These changes were closely related to the loss of bone mass in astronauts during spaceflight (Whedon et al, 1976;Rambaut and Johnston, 1979;Tilton et al, 1980;Caillot-Augusseau et al, 1998;Man et al, 2022). This indicates that the regenerating scales sensitively respond to the three-dimensional clinostat simulating microgravity conditions similar to those that astronauts are subjected to during space flights.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition, the mRNA expression levels of the osteoblastic markers, Col1a1 and Ocn, in the simulated microgravity treatments were significantly lower than that in the 1G control (Figure 5). These changes were closely related to the loss of bone mass in astronauts during spaceflight (Whedon et al, 1976;Rambaut and Johnston, 1979;Tilton et al, 1980;Caillot-Augusseau et al, 1998;Man et al, 2022). This indicates that the regenerating scales sensitively respond to the three-dimensional clinostat simulating microgravity conditions similar to those that astronauts are subjected to during space flights.…”
Section: Discussionmentioning
confidence: 94%
“…We found that Rankl mRNA expression levels in the regenerating scales after microgravity treatments were significantly higher than that of the mRNA expression levels in the control (1G) scales (Figure 3). OPG is a circulating decoy receptor for RANKL and downregulates osteoclastogenesis, resulting from the inhibition of the interaction between RANKL and RANK (Man et al, 2022). Thus, the RANK/RANKL/OPG system has an essential function in osteoclastogenesis regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This decreases their capacity to maintain healthy bone and skeletal muscle tissue, and the ability to respond and adapt to the mechanical environment. Additionally, commitment of BMSCs down the adipogenic lineage reduces the ability of bone and skeletal muscle tissue to regenerate and recover following injury 23 24. These effects are similar to what is seen with ageing, and thus, microgravity research could prove useful for understanding the process of ageing 15 22 25…”
Section: Effects Of Spaceflight On Select Physiological Systems and H...mentioning
confidence: 99%